2016
DOI: 10.3386/w21865
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Effects of Cultural Relevance: Evidence from an Ethnic Studies Curriculum

Abstract: An extensive theoretical and qualitative literature stresses the promise of instructional practices and content aligned with the cultural experiences of minority students. Ethnic studies courses provide a growing but controversial example of such "culturally relevant pedagogy." However, the empirical evidence on the effectiveness of these courses is limited. In this study, we estimate the causal effects of an ethnic studies curriculum piloted in several San Francisco high schools. We rely on a "fuzzy" regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
178
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(191 citation statements)
references
References 2 publications
9
178
1
3
Order By: Relevance
“…But even within organizations and partnerships that are organized around shared equity goals, visibility can obligate forms of translation across hierarchies of power and epistemology that shift centers of gravity away from studying valued practices and forms of learning on their own terms. For example, arguments for implementing Ethnic Studies courses at the high school level have benefited from recent research on the causal effects of such courses (Dee & Penner, 2016). At the same time, the argument that Ethnic Studies should be required because it increases student achievement based on normative measures risks discounting a wider set of developmental outcomes that may be deeply valued by students, teachers and families, but overlooked by standard frames of achievement.…”
Section: Downloaded By [University Of Tennessee Knoxville] At 13:42 mentioning
confidence: 99%
“…But even within organizations and partnerships that are organized around shared equity goals, visibility can obligate forms of translation across hierarchies of power and epistemology that shift centers of gravity away from studying valued practices and forms of learning on their own terms. For example, arguments for implementing Ethnic Studies courses at the high school level have benefited from recent research on the causal effects of such courses (Dee & Penner, 2016). At the same time, the argument that Ethnic Studies should be required because it increases student achievement based on normative measures risks discounting a wider set of developmental outcomes that may be deeply valued by students, teachers and families, but overlooked by standard frames of achievement.…”
Section: Downloaded By [University Of Tennessee Knoxville] At 13:42 mentioning
confidence: 99%
“…School environments that promote Aboriginal cultural retention, possibly by offering language courses, may mitigate some of the negative school experiences of Aboriginal children that could be exacerbated by parental residential school attendance (O'Gorman & Pandey, 2015). The inclusion of culturally relevant curricula has also been shown in other minority groups to significantly increase school retention and performance (Dee & Penner, 2016). It has been shown that teachers with similar characteristics to their students (such as race or ethnicity) are associated with improved student outcomes (Fairlie, Hoffmann, & Oreopoulos, 2011;Hoffmann & Oreopoulos, 2009) and this has been shown in Aboriginal contexts as well (O'Gorman & Pandey, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research demonstrates, for example, the educational benefits associated with matching black and Hispanic students with same-race teachers (Dee 2004, Fox 2016, Gershenson et al 2016, Irizarry 2015) and curricula that reflect their experiences (Dee & Penner 2016). …”
Section: Forms Of Educational Categorical Inequalitymentioning
confidence: 99%